2012
DOI: 10.1042/bj20111885
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of the Pdp1 PWWP domain reveals its unique binding sites for methylated H4K20 and DNA

Abstract: Methylation of H4K20 (Lys(20) of histone H4) plays an important role in the regulation of diverse cellular processes. In fission yeast, all three states of H4K20 methylation are catalysed by Set9. Pdp1 is a PWWP (proline-tryptophan-tryptophan-proline) domain-containing protein, which associates with Set9 to regulate its chromatin localization and methyltransferase activity towards H4K20. The structure of the Pdp1 PWWP domain, which is the first PWWP domain identified which binds to methyl-lysine at the H4K20 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
74
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 44 publications
4
74
0
Order By: Relevance
“…Moreover, the PWWP domain o f D N M T 3 a e x h i b i t s n o c l e a r p r e f e r e n c e f o r hemimethylated, double-methylated, or CpG-containing double-stranded DNA sequences (Purdy et al 2010). Finally, consistent with previous results, the PWWP domains of Schizosaccharomyces pombe Pdp1, as well as the human proteins LEDGF/p75 and ZMNYD11 were shown to bind DNA nonspecifically (Qiu et al 2012;van Nuland et al 2013;Eidahl et al 2013;Wang et al 2014). In contrast to these data, Yang and Everett (2007) have shown that the PWWP domain of HGDF is able to specifically recognize a 37-bp DNA element common to the promoter of SMYD1, arguing about the specificity of interaction between PWWP domains and DNA.…”
Section: Structural Features Of Pwwp Domainssupporting
confidence: 77%
See 4 more Smart Citations
“…Moreover, the PWWP domain o f D N M T 3 a e x h i b i t s n o c l e a r p r e f e r e n c e f o r hemimethylated, double-methylated, or CpG-containing double-stranded DNA sequences (Purdy et al 2010). Finally, consistent with previous results, the PWWP domains of Schizosaccharomyces pombe Pdp1, as well as the human proteins LEDGF/p75 and ZMNYD11 were shown to bind DNA nonspecifically (Qiu et al 2012;van Nuland et al 2013;Eidahl et al 2013;Wang et al 2014). In contrast to these data, Yang and Everett (2007) have shown that the PWWP domain of HGDF is able to specifically recognize a 37-bp DNA element common to the promoter of SMYD1, arguing about the specificity of interaction between PWWP domains and DNA.…”
Section: Structural Features Of Pwwp Domainssupporting
confidence: 77%
“…The PWWP domains of DNMT3a/b contain a bundle of five α-helices (Qiu et al 2002;Wu et al 2011). On the other hand, those of BRPF1, HDGF, HDGF2, and Pdp1 are composed of two α-helices connected by a loop (Lukasik et al 2006;Vezzoli et al 2010;Wu et al 2011;Qiu et al 2012). Recently, the structure of the PWWP domain from LEDGF/ p75 revealed a C-terminal region with less helical content than its counterparts.…”
Section: Structural Features Of Pwwp Domainsmentioning
confidence: 99%
See 3 more Smart Citations